Implementation of Public Information Disclosure Policy in Realizing Good Corporate Governance - Yudi Nur Supriadi; Iwan Kresna Setiadi; Esaka Pratala (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2023)
The Indonesian Aviation Navigation Service Organizing Agency, operating as a State-Owned Enterprise, is obligated to uphold the tenets of Good Corporate Governance per the Minister of State-Owned Enterprises Regulation Number 01 of 2011. This commitment extends to the implementation of policies outlined in Law Number 14 of 2008, specifically addressing the Openness of Public Information. A nuanced analysis, rooted in George Edward's implementation theory, delves into the complexities of how the Information and Documentation Management Officer at AirNav Indonesia navigates the communication dynamics, resource allocation, organizational disposition, and bureaucratic structure inherent in executing public information disclosure policies. Employing qualitative methods and triangulation techniques, this study unravels the intricate interplay of these components, illustrating that effective implementation transcends procedural adherence to embody a comprehensive orchestration of transparency, accountability, responsibility, independence, and fairness within the context of public information disclosure. The Information and Documentation Management Officer emerges as a pivotal figure, strategically aligning these elements to achieve a robust realization of the principles of good corporate governance.